2013
DOI: 10.1016/j.bbrc.2012.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin induces MMP2 expression in human prostate cancer cells

Abstract: High-grade prostate cancers express high levels of matrix metalloproteinases (MMPs), major enzymes involved in tumor invasion and metastasis. However, the tumor cell lines commonly employed for prostate cancer research express only small amounts of MMPs when cultivated as monolayer cultures, in common culture media. The present study was conducted to ascertain whether culture conditions that include fibronectin can alter MMP2 and MMP9 expression by the human prostatic epithelial cell lines RWPE-1, LNCaP and PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…In ovarian cancer, FN1 secreted from the human peritoneal tissue induces MMP9 expression and the invasion of ovarian cancer cell lines (Shibata et al, 1997). FN1 also induces MMP9 expression in human laryngeal carcinoma cells (Sen et al, 2010) and MMP2 expression in human prostate cancer cells (Moroz et al, 2012). We showed herewith that FN1 is a direct target of SOX2 (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…In ovarian cancer, FN1 secreted from the human peritoneal tissue induces MMP9 expression and the invasion of ovarian cancer cell lines (Shibata et al, 1997). FN1 also induces MMP9 expression in human laryngeal carcinoma cells (Sen et al, 2010) and MMP2 expression in human prostate cancer cells (Moroz et al, 2012). We showed herewith that FN1 is a direct target of SOX2 (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Naiki-Ito et al [42] also reported that ellagic acid, the precursor of UA, at high concentrations (75-125 μM) promotes apoptosis, activates caspase 3 and reduces Bcl-2 protein levels in LNCaP cells. Interestingly, some studies assessed that cross talk between tumor cells and extracellular matrix proteins, when present in culture systems, leads to behavioral changes in tumor cell biology, such as increased adherence to substrates, increased resistance to chemotherapeutic agents and resistance to apoptosis [43]. Thus, the effect of UA on tumor cell survival is probably multifactorial, considering that the extracellular protein, fibronectin (encoded by FN-1), was down-regulated by UA incubation and appeared as a node gene in our BAN.…”
Section: Discussionmentioning
confidence: 99%
“…The two important molecules MMP and uPA are involved in cancer cell invasion, motility, and tumor dormancy [15][16][17]. Based on the results of both the migration assay and invasion assay in PC3 cells, we anticipated that desmopressin used as a monotherapy may have anti-metastatic potential.…”
Section: Upa-mmp Pathway Mediates the Desmopressin-induced Migration mentioning
confidence: 99%